2012
DOI: 10.1177/0018726712445100
|View full text |Cite
|
Sign up to set email alerts
|

Escaping bullying: The simultaneous impact of individual and unit-level bullying on turnover intentions

Abstract: In this study, we investigate the simultaneous impact of, and interaction between, being the direct target of bullying and working in an environment characterized by bullying upon employees’ turnover intentions. Hierarchical linear modeling analysis of a sample of 41 hospital units and 357 nurses demonstrates that working in an environment characterized by bullying increases individual employees’ turnover intentions. Importantly, employees report similarly high turnover intentions when they are either the dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 75 publications
(84 reference statements)
3
75
0
Order By: Relevance
“…The victim of bulling behavior (employee) feels to be socially disconnected and such feeling impedes variety of behavioral responses (Leymann, 1996) one of such response having negative opinion about the organization and victim's turnover intension (Houshmand et al, 2012). Therefore, it can be assumed that an employee's facing bullying behavior would have negative opinion about the organization and would involve in creating negative word of mouth for the organization.…”
Section: Workplace Bulling Behavior and Relationship Continuitymentioning
confidence: 99%
“…The victim of bulling behavior (employee) feels to be socially disconnected and such feeling impedes variety of behavioral responses (Leymann, 1996) one of such response having negative opinion about the organization and victim's turnover intension (Houshmand et al, 2012). Therefore, it can be assumed that an employee's facing bullying behavior would have negative opinion about the organization and would involve in creating negative word of mouth for the organization.…”
Section: Workplace Bulling Behavior and Relationship Continuitymentioning
confidence: 99%
“…Clark (2007) advances that a significant relationship exists between corporate psychopathy, employee withdrawal, disenfranchisement, poor leadership, and suboptimal performance of employees. It is also proposed that the attitude and activities of corporate psychopaths will translate to absenteeism and employee turnover (Houshmand et al, 2012). Empirical study by Mathieu et al (2014) established that corporate psychopathy will result in decreased employee wellbeing, job dissatisfaction and poor job attitudes.…”
Section: Corporate Psychopathymentioning
confidence: 99%
“…Empirical findings have reported several outcomes of corporate psychopathy (Clark, 2007;Houshmand et al, 2012;Boddy, 2014;Mathieu et al, 2014). Corporate psychopaths usually belong to the upper echelon in many organizations, and their predatory nature portends adverse effects on employees who may become preys to their antics.…”
Section: Hypotheses Formulationmentioning
confidence: 99%
“…The choice among these alternatives is determined by the situation and job constraints. For example, research findings indicated that bullying has impact on victims' turnover intention (Houshmand, O'Reilly, Robinson & Wolff, 2012), however, bullied employees would not leave unless alternative employment is first available (Gerhart, 1990). Subsequently some employees will unwillingly remain in unwanted employment because of some constraints on quitting.…”
Section: Workplace Bullying-unethical Behaviorsmentioning
confidence: 99%